Beyond skin white spots: Vitiligo and associated comorbidities - Hu, Zhonghui; Wang, Tao (Frontiers in Medicine, 2023)
Vitiligo is a common depigmentation disorder of an unknown origin characterized by the selective loss of melanocytes, resulting in typical white macules and patches. However, vitiligo is now recognized as more than just a skin disease, what a dermatologist observes as a white spot of skin is just the “tip of the iceberg” of the condition. We attempt to clarify the classification of comorbidities associated with vitiligo from various reviews and reports, and describe their possible pathogenesis. In conclusion, the literature provides evidence of an association between vitiligo and ocular and auditory abnormalities, autoimmune disorders, other dermatological diseases, metabolic syndrome and related disorders, and psychological diseases. These associations highlight the importance of a multidisciplinary approach in managing vitiligo patients.